Transgender and gender non-conforming students in schools: one school district's approach for creating safety and respect. Issue 2 (4th March 2019) - Goodrich, Kristopher; Barnard, Janalee
ABSTRACT: For more than two decades, there has been a concerted effort in Albuquerque Public School District (APS) in Albuquerque, New Mexico, USA to educate adults about LGBTQ students and the need for advocacy so that these students have the same access to education as other students in a safe and respectful environment. Populations within the district that have received less attention include students who identify as transgender and gender non-conforming. This manuscript describe APS's work with transgender and gender nonconforming students and the use of the American Institutes for Research's Improving Emotional and Behavioral Outcomes for LGBT Youth Action Planning Tool, as a means to evaluate the district's plan and activities, which led to an administrative directive regarding non-discrimination based upon gender identity and expression. The information here is offered as a resource to other school districts to learn from our successes and challenges, and perhaps to undertake similar work in their own school context.